Peningkatan Hasil Belajar Peserta Didik Dengan Model Pembelajaran Snowball Throwing Pada Pembelajaran Dasar Telekomunikasi - Mawardi Mawardi; Fathiah Fathiah; Khairun Annas (PTE FTK UIN Ar-Raniry, 2022)
Based on the previous observations at SMKN 5 Telkom Banda Aceh on Basic Telecommunication subject, it presented that most students still lack of enthusiasm and interest in learning. They prefer did another in the class other than study. This problems faced the students in the classroom atmosphere noisy and disrupted learning activities. This has an impact on the students’value or score which got bad and down. The purpose of this study was to determine the learning outcomes of students and their responses to the application of the Snowball Throwig learning model in basic telecommunication learning at SMKN 5 Telkom Banda Aceh. This study uses a quasi-experimental design with one group pretest and posttest. By using test sheets and questionnaires, this research was carried out using quantitative data analysis techniques. The results showed that the learning outcomes of students increased significantly with the average pretest score of 28.50 increasing to the posttest average value of 71.00. So it can be concluded that there is an increase in student learning outcomes in Basic Telecommunication learning at SMKN 5 Telkom Banda Aceh with the application of the Snowball Throwing learning model. In addition to learning outcomes, student response data is good. This is evidenced by looking at the student's response to the positive statement of the questionnaire on average above 75%. It can be concluded that the application of the snowball throwing learning model is able to improve student learning outcomes and attract students' interest in learning.